"Pressão de vapor": uma propriedade importante da substância - Souza, Cecilia de (2021)
In our daily lives, it is common to observe several Chemical processes, including evaporation. This is directly linked to what in chemistry we call vapor pressure, a very important concept to understand some methods of obtaining substances in industry and to understand common phenomena. This concept is usually presented to students in the 2nd year of High School (E.M) in the referencial curricular in the content of colligative properties. However, this content is not part of the curricula of public schools in the State of Mato Grosso do Sul (MS). Thus, the present work is a suggestion to be carried out with students in the 1st year of E.M., with the use of an accessible resource. In this way, the product presented to the Professional Master's Program in Chemistry in the National Network - PROFQUI, goal to offers to the teacher and students the using up of a hypertext, involving concepts of Chemistry, to assist in the construction knowledge by students in a more significant. The hypertext was chosen because it proposes a “learning trail” where the student, when going through it, will have access to concepts of vapor pressure, the history of atmospheric pressure, pressure units andalso a “simulation”. Thus completing the resources present in Brazilian public schools and remedying, to a certain extent, the scarcity of available materials related to the theme of vapor pressure.